mRNA Vaccine Technology Beyond COVID-19 - Sola Oloruntimehin; Florence Akinyi; Michael Paul; Olumuyiwa Ariyo (Vaccines, 2025)
Background/Objectives: Since their approval in early 2020, mRNA vaccines have gained significant attention since the COVID-19 pandemic as a potential therapeutic approach to tackle several infectious diseases. This article aims to review the current state of mRNA vaccine technology and its use against other diseases. Methods: To obtain accurate and reliable data, we carefully searched the clinicaltrial.gov and individual companies’ websites for current ongoing clinical trials reports. Also, we accessed different NCBI databases for recent articles or reports of clinical trials, innovative design of mRNA vaccines, and reviews. Results: Significant progress has been made in the design and improvement of mRNA vaccine technology. Currently, there are hundreds of ongoing clinical trials on mRNA vaccines against different cancer types, infectious diseases, and genetic and rare diseases, which showcase the advancement in this technology and their potential therapeutic advantages over traditional vaccine platforms. Finally, we predict what could be a potential future direction in designing more effective mRNA vaccines, particularly against cancer. Conclusions: The results of many of the ongoing clinical trials have shown significant positive outcomes, with many of the trials already at Phase III. Despite this outlook, however, some have been terminated or withdrawn for several reasons, some of which are not made available. This means that despite the advancement, there is a need for more research and critical evaluation of each innovation to better understand their immunological benefits and long-term effects.